Sequential intravesical gemcitabine and docetaxel therapy in patients with nonmuscle invasive bladder cancer: a systematic review and meta-analysis - Kawada, Tatsushi; Yanagisawa, Takafumi; Araki, Motoo; Pradere, Benjamin; Shariat, Shahrokh F (Current opinion in urology, 2023)
PURPOSE OF REVIEW: Shortages in intravesical Bacillus Calmette-Guérin (BCG) immunotherapy represent a challenge in the management of high-risk nonmuscle invasive bladder cancer (HR-NMIBC). This study aimed to review the efficacy and safety of intravesical gemcitabine (GEM) and docetaxel (DOCE) for BCG-naive and unresponsive HR-NMIBC. RECENT FINDINGS: We identified six studies eligible for quantitative analysis through a systematic search according to the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) statement. In the two studies in the BCG-naive setting, 1-year and 2-year pooled recurrence-free survival (RFS) were 86 and 84%, respectively. In the two studies in the BCG unresponsive setting, 6-month, 1-year and 2-year pooled high-grade recurrence-free survival (HG-RFS) were 80, 66 and 51%, respectively. Cumulative data from four studies revealed that 2.3% of patients could not complete induction therapy and 6.9% experienced treatment delay or dose reduction due to adverse events. SUMMARY: Despite the preliminary data and based on a small sample size, intravesical GEM/DOCE therapy is a highly promising combination yielding an effective and well tolerated alternative to BCG when indicated. Further large, well designed comparative studies with BCG are needed.
Keywords: aplikace intravezikální; Docetaxel; Neoplasm Invasiveness; gemcitabin; Urinary Bladder Neoplasms; adjuvancia imunologická; Adjuvants, Immunologic; Humans; Administration, Intravesical; nádory močového měchýře; BCG vakcína; BCG Vaccine; lokální recidiva nádoru; Neoplasm Recurrence, Local; Gemcitabine; docetaxel; invazivní růst nádoru; lidé